2019
DOI: 10.4103/jfmpc.jfmpc_272_18
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts women with breast cancer face with: A qualitative study

Abstract: Background and Aim: The prevalence of cancer in women under 50 years of age has been increased in recent years. Cancer treatment methods can lead to infertility in women with cancer. Fertility and childbearing, as the most important conflicts in the life of women with breast cancer, significantly affect their quality of life. Materials and Methods: This research is a qualitative study of content analysis type. Purposeful sampling and semi-structured individual interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…It is common for breast cancer patients to experience physical, social, sexual, and psychological (including anxiety and depression) problems. 6,7,8,7,45 Studies showed that having timely and appropriate information helps breast cancer patients to involve in an informed decision of their treatment process, learn about the disease, and control their life and coping mechanism. It also improves their quality of life and lowers their anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is common for breast cancer patients to experience physical, social, sexual, and psychological (including anxiety and depression) problems. 6,7,8,7,45 Studies showed that having timely and appropriate information helps breast cancer patients to involve in an informed decision of their treatment process, learn about the disease, and control their life and coping mechanism. It also improves their quality of life and lowers their anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, previous researches revealed that the relation of breast cancer with body image is one of the reasons for patients to experience a worsening problem and to have a poor quality of life. 6,7 Because treatment of breast cancer is complex and prolonged, it needs active involvement of patients themselves. It is known that treatment for breast cancer is prolonged and complex, it needs the active involvement of the patients themselves.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the process of surgery decision-making for newly diagnosed BCa patients is not simple in clinical practice, and most patients have difficulty making decisions due to certain situations, leading to the occurrence of decision conflict (Ghaemi et al, 2019).…”
mentioning
confidence: 99%
“…In fact, a qualitative study in 2019 exploring the conflicts faced by breast cancer patients concluded that fears related to future child-bearing was the primary dilemma for patients considering different treatment methods and plans. 5 The goal of oncofertility, or fertility preservation prior to cancer treatment, is to address this dilemma.…”
Section: Introduction 11 Cancer Survival and Fertility Preservationmentioning
confidence: 99%